Tourist and Recreational Potential of the Territory: Analysis Methodology - R.S Garifullina; F. M. Safin (Indonesian Journal of Law and Economics Review, 2020)
The introduction of the term "potential" into the official turnover of tourism science promotes the methodology of research. Tourist - recreational potential of the territory in this case refers to the scientific category, the analysis of the content, whose structure is a necessary condition for understanding the essence of the tourist destination. All this actualizes the necessity of complex research of tourist - recreational potential of the territory. We believe that it is not only permissible, but it is quite necessary to use the concept "tourist - recreational potential of the territory", including in the regulatory documents, as it is the most complete, comprehensively allows to reveal problems and prospects of tourism development in the region. Firstly, the tourist and recreational potential, being different in content, is present at the territory simultaneously, accompanying each other, implemented in it, being of interest to the tourist. Secondly, there is no territory where there is a recreational potential, which cannot be supplemented with tourist potential, and vice versa. Third, the identification of tourist - recreational potential of the territory allows to develop an algorithm for its transformation into tourist-recreational resources, to determine the goals and objectives for the formation, promotion and implementation of the tourist product, tourist brand of the territory.